Complex rupture of the M6.3 2015 March 10 Bucaramanga earthquake: evidence of strong weakening process (2016)
We use seismic waves for a magnitude 6.3 intermediate-depth (160?km) earthquake in the Bucaramanga Nest, Colombia, to infer a complex rupture process with two distinct stages, characterized by different rupture velocities possibly controlled by the evolution of strength on the fault. Our integrated data processing permitted to precisely characterize the multistage rupture and the presence of a strong weakening event. The resulting seismic radiation is interpreted as resulting from an extreme weakening due to a cascading thermal shear runaway, with an initial inefficient radiation process followed by a fast and dynamic efficient rupture. Our results imply dynamic complexity of the seismic rupture deep inside the Earth, and may help to give some new insights about the physical mechanism of intermediate-depth earthquakes.